Modern Greek Constructional Phrasemes with Antonymous Verbs: Χ τον ανε- βάζει, Χ / Y τον κατεβάζει and Χ μπαίνει, Χ βγαίνει - E. S. Onufrieva (Научный диалог)
The paper presents the results of the corpus and lexicographical analysis of two Modern Greek constructional phrasemes (a class of phraseologisms distinguished by A. N. Baranov and D. O. Dobrovol’skij) with antonymous verbs in their fixed part — Χ τον ανεβάζει, Χ / Y τον κατεβά- ζει and Χ μπαίνει, Χ βγαίνει. It is noted that though these constructional phrasemes have different meanings and dissimilar functions in the sentence there is structural and semantic similarity between them. The two phrasemes represent a rhyming two-part structure, whose main lexical “anchors” are antonymous locative verbs expressing a counter-directional movement of a subject or an object in space. It is shown that the pairs of the antonymous verbs become desemanticized and the relation of antonymy between them becomes lost as they form the fixed part of the constructional phrasemes. It is emphasized that at the same time the original locative meaning of the verbs adds it imagery to the semantic content of these phrasemes, becoming the basis of their inner form, and determines some part of their meaning — the meaning of multitude of repeating situations. The paper also takes into consideration some idiomatical constructions of other languages that have similar meanings to those of the Greek constructional phrasemes. It is demonstrated that many of these constructions are also formed by means of locative antonyms, which provides evidence to suggest that this type of inner form is frequent among phraseologisms denoting multitude of repeating situations.